Evaluation of the zinc succinate toxic eﬀect on the cerebral cortex of rat - G. A. Piavchenko; A. G. Alekseev; E. S. Seryogina; O. A. Stelmashchuk; E. A. Zherebtsov; A. V. Dunaev; S. L. Kuznetsov (Сеченовский вестник, 2019)
Background. Anthropogenic human activity contributes to the inclusion of zinc compounds in the biological cycle in areas where there is pollution with this metal. This leads to the accumulation of the substance in organs and tissues, which can have a neurotoxic eﬀect on the body. Aim. To evaluate the toxic eﬀect of zinc succinate on the structure and function of the cerebral cortex of laboratory rats. Materials and methods. The study was performed on 12 Wistar male rats aged 2 months. The animals were divided into 2 groups: control and experimental, 6 rats each. Within 30 days, the animals of the experimental group were intragastrically injected with a solution containing zinc succinate in a dose of 100 mg/kg. The rats from group 1 served as intact controls. Fluorescent analysis of coenzyme activity of the brain was performed, for which excitation was used at wavelengths of 365 nm and 450 nm, which corresponds to the reduced form of nicotinamide adenine dinucleotide (NADH) and ﬂavin adenine dinucleotide (FAD); morphological analysis of the motor cortex of the cerebral hemispheres.Results. Analysis of ﬂuorescence spectra demonstrated a statistically signiﬁcant decrease in its intensity in the experimental group for the coenzyme NADH (0.855 [0.092]) compared with the control (0.709 [0.062]); p